2010
DOI: 10.1111/j.1365-2443.2009.01368.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple roles of PPARα in brown adipose tissue under constitutive and cold conditions

Abstract: Peroxisome proliferator-activated receptor a (PPARa) is a member of the nuclear receptor family, regulating fatty acid degradation in many organs. Two-dimensional SDS-PAGE of brown adipose tissue (BAT) from PPARa-null mice produced a higher-density spot. Proteomic analysis indicated that the protein was pyruvate dehydrogenase b (PDHb). To observe PDHb regulation in BAT, the organ was stimulated by long-term cold exposure, and the activities of associated enzymes were investigated. Histological and biochemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
14
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
(105 reference statements)
6
14
0
2
Order By: Relevance
“…In a focused interrogation of potential downstream mediators, we observed that BAIBA significantly increases the expression of PPARα in white adipocytes both in vitro (2.4-fold increase, Figure 5A) and in the inguinal white fat depot in vivo (2.2-fold increase, Figure 5B). PPARα is a key transcription factor known to stimulate the expression of UCP-1(Bostrom et al, 2012; Komatsu et al, 2010). We were interested to find that the selective PPARα antagonist GW6471 significantly abrogated the BAIBA-stimulated increase in thermogenic gene expression in primary adipocytes (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
“…In a focused interrogation of potential downstream mediators, we observed that BAIBA significantly increases the expression of PPARα in white adipocytes both in vitro (2.4-fold increase, Figure 5A) and in the inguinal white fat depot in vivo (2.2-fold increase, Figure 5B). PPARα is a key transcription factor known to stimulate the expression of UCP-1(Bostrom et al, 2012; Komatsu et al, 2010). We were interested to find that the selective PPARα antagonist GW6471 significantly abrogated the BAIBA-stimulated increase in thermogenic gene expression in primary adipocytes (Figure 5C).…”
Section: Resultsmentioning
confidence: 99%
“…The activation of PGC-1␣ gene expression by PPAR␣ may provide a mechanism for concerted induction of thermogenic genes (UCP1, fatty acid oxidation genes, mitochondrial genes) in response to the enhanced intracellular availability of fatty acids sensed by PPAR␣. PPAR␣-null mice, despite being resistant to cold and having overtly normal BAT morphology (35, 36, 30), show thermogenesis-related disturbances in response to cold stress, such as a marked suppression of BAT growth concurrent with a prominent decrease in fatty acid oxidative and thermogenic activities (37,38,18). Consistent with our current findings of a role for PPAR␣ in the control of PGC-1␣ gene transcription, we observed that PGC-1␣ gene expression is decreased in PPAR␣-null BAT both under basal conditions and in response to acute thermogenic activation.…”
Section: Discussionmentioning
confidence: 99%
“…One potentially important transcription factor induced by Fndc5, identified using gene expression arrays, was PPARα This nuclear receptor has been shown to drive UCP1 expression and several other genes involved in browning of adipose cells 10 . PPARα is increased 3-fold at the mRNA level by Fndc5 treatment (Fig.…”
Section: Pparα Acts Downstream Of Fndc5 To Promote a Thermogenic/browmentioning
confidence: 99%